Impact of air pollution on groundwater contamination through water reservoir. Issue 3 (4th May 2023) - Samanta, Animesh; Chatterjee, Ayan; Singh, Mritunjay Kumar
ABSTRACT: In this article, an incisive analysis had been carried out to investigate the impact of air pollution on groundwater through a water reservoir. The primary objective of the present work was to develop a mathematical model that shows the direct impact of air pollution on groundwater contamination. The advection-dispersion equation (ADE) was considered to model the contaminant transport through the different media. Due to its inherent complexities, contaminant transport through the different domains was often difficult to model. To overcome it, the simple solution was to consider different velocities and dispersion for different domains. It was considered that the air zone was directly connected with the groundwater through a large water body. Initially, water body and aquifer had been considered contaminant free along with the flux type boundary condition at the semi-infinite part of the boundary. The model had been solved analytically using Laplace transformations. The current study demonstrates that depending upon the length of the medium the impact of contaminant would vary significantly. The air pollution source height had a direct impact on the contaminant concentration level in the aquifer aquitard system. The current study also illustrates that around 25% of air pollutants were induced in the groundwater.